Forced vital capacity, airway obstruction and survival in a general population sample from the USA. Issue 1 (26th October 2010) - Burney, P G J; Hooper, R
Abstract : Background: Many studies show a link between forced expiratory volume in 1 s (FEV1 ) and survival in the general population and this has been interpreted as a link between airway obstruction and survival. However, the observation that vital capacity is also associated with survival weakens this interpretation. Methods: Data on spirometry and survival were taken from the Atherosclerosis Risk in Communities (ARIC) limited access dataset. Survival among 7489 participants with usable spirometry and complete data was regressed against measures of ventilatory function after controlling for many other factors likely to be associated with survival. Results: Survival was strongly associated with forced vital capacity (FVC) after adjustment for FEV1, but not the other way round. The fully adjusted hazard ratio (HR) associated with high FVC was 0.90 in men (95% CI 0.80 to 1.00; p=0.049) and 0.82 in women (95% CI 0.70 to 0.95; p=0.01). This compares with 0.98 for FEV1 in men (95% CI 0.90 to 1.07; p.0.72) and 1.01 in women (95% CI 0.89 to 1.15; p=0.84). There was no association between survival and airway obstruction as measured by the FEV1 /FVC ratio. Conclusions: FVC but not airway obstruction predicts survival in asymptomatic adults without chronic respiratory diagnoses or persistent respiratory symptoms. The association is not explained by age, anthropometry, smoking, income occupation or blood pressure. As FVC later in life, cardiovascular risk, type II diabetes mellitus and low-grade systemic inflammation are all associated with poor fetal growth, these other conditions may be partly responsible for the poor survival in those with low FVC.